An unexceptional exception: Golf, pesticides, and environmental regulation in Canada. (June 2016) - Millington, Brad; Wilson, Brian
This paper features a critical examination of recent legislation banning cosmetic pesticide applications in the province of Ontario, Canada. It focuses in particular on the exemption of golf courses from the province's Cosmetic Pesticides Ban Act of 2009. Drawing from a wide range of materials, the authors first contextualize Ontario's recent law through an overview of the historical development of pre- and post-market pesticide regulation in Canada. This includes a review of the fierce debates that have at times arisen between pro- and anti-chemical factions. From there, the authors evaluate the Cosmetic Pesticides Ban Act. In one sense, the law – and especially golf's exemption from the law – is said to exemplify "environmental managerialist" decision-making, whereby governments must satisfy a "dual mandate" of promoting economic growth and environmental sustainability simultaneously. In another, related way, it is seen as demonstrative of an "ecological modernist" approach to environmental problems in which industry-led, technologically-advanced solutions are privileged above others. Taken together, golf's "special status" in Ontario's new pesticide legislation is deemed reflective of a wider trend towards neoliberal environmental policy making in Canada. It is also regarded in closing as a reason for future research into sport and environmental policy.